Pemberian Scaffolding Berdasarkan Kesalahan Berpikir Siswa Dalam Memecahkan Masalah Matematika - Rosdiana Kaka; Anton Prayitno; Abdul Hamid (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2018)
This research was aimed to elaborate on the form of scaffolding given by learners on algebra problem-solving. The approach used is descriptive qualitative. The study conducted in a junior high school in Malang Regency with 25 students and only two students were selected as research subjects to be given scaffolding level 2. Data collection method begins by requiring learners to solve algebra and next identify the pattern of mistakes or mistakes. Learners who have wrong answers, used as research samples. The results prove the form of scaffolding given the subject. If the subject experiences an error in understanding the problem, the scaffolding is given asking the subject to re-read the problem properly and carefully and give direction questions. However, if the subject has difficulty in making the planning of the settlement, the scaffolding given is giving the subject the opportunity to rearrange the design of the right answer. If the subject experiences an error in carrying out the planning, the scaffolding given is asking the subject to pay attention to the mathematical concept and to be careful in operating algebra.